Distinct subcellular localization of the neuronal marker HuC/D reveals hypoxia‐induced damage in enteric neurons. Issue 8 (25th May 2014) - Desmet, A.‐S.; Cirillo, C.; Vanden Berghe, P.
Abstract Background Correct neuronal identification is essential to study neurons in health and disease. Although commonly used as pan‐neuronal marker, HuC/D's expression pattern varies substantially between healthy and (patho)physiological conditions. This heterogenic labeling has received very little attention. We sought to investigate the subcellular HuC/D localization in enteric neurons in different conditions. Methods The localization of neuronal RNA‐binding proteins HuC/D was investigated by immunohistochemistry in the mouse myenteric plexus using different toxins and caustic agents. Preparations were also stained with Sox10 and glial fibrillary acidic protein (GFAP) antibodies to assess enteric glial cell appearance. Key Results Mechanically induced tissue damage, interference with the respiratory chain and oxygen (O2) deprivation increased nuclear HuC/D immunoreactivity. This effect was paralleled by a distortion of the GFAP‐labeled glial network along with a loss of Sox10 expression and coincided with the activation of a non‐apoptotic genetic program. Chemically induced damage and specific noxious stimuli did not induce a change in HuC/D immunoreactivity, supporting the specific nature of the nuclear HuC/D localization. Conclusions & Inferences HuC/D is not merely a pan‐neuronal marker but its subcellular localization also reflects the condition of a neuron at the time of fixation. The functional meaning of this change in HuC/D localization is not entirely clear, but disturbance in O2 supply in combination with the support of enteric glial cells seems to play a crucial role. The molecular consequence of changes in HuC/D expression needs to be further investigated.